Analysis of the Factors Causing Occupational Accidents at UPT Balai Yasa PT KAI (Persero) Yogyakarta - Erni; Widodo Hariyono (Periodicals of Occupational Safety and Health, 2024)
Background : UPT Balai Yasa Yogyakarta is a subsidiary of Kereta Api Indonesia (Persero) which engaged in infrastructure facilities units and a locomotive repair shop that operates only on the island of Java and is the general workshop that maintain steam locomotives, passenger and freight cars. To anticipate increasing occupational accidents in production workers, in need of research to determine the factors that influence the occurence of occupational accidents in UPT Balai Yasa Yogyakarta. The factors that cause workplace accidents will be investigated views of human factors and environmental factors. Methods: The study was a descriptive study with a qualitative approach. The subjects in this study were production workers who had experienced workplace accidents by 17 people. The tool used was in the form of an interview guide, observation, and documents. Results: (1) The first is human factors; many workplace accident happen due to lack of understanding of workers, less skilled, less education, physical disability, body position while working less comfortable, not orderly use of PPA, sensitivity of the senses and work beyond working hours resultingin fatigue and productivity employment declined. (2) The second is environmental factors; the workplace is adequate production conditions in the building but not entirely safe for workers. Workplace accidents occur because the tools used are too old, unbelievably disturbing noise threshold, there is a fire in the workplace and the nature of the work does contain potential hazard. Conclusion: Human factors such as labor imbalance (body postures, physical disability, sensory sensitivity), less education (less experience, less skilled), disorderly use of PPA, work beyond working hours and environmental factors such as equipment have been unsuitable, there was a fire in the workplace and the nature of any hazardous ocuupation causes of accidents in UPT Balai Yasa Yogyakarta.